Cambios tributarios de los regímenes y su impacto en los negocios populares de víveres del sector urbano de la parroquia El Triunfo cantón La Maná, de la provincia Cotopaxi período 2021-2022. - Plasencia Palomo, Jessenia Nathaly (2023)
The present research work focused on analyzing the new RIMPE tax regime for popular food businesses located in the La Maná canton, El Triunfo parish, for the development that a methodology was used that involved quantitative, qualitative approaches, types of research, bibliographic, field, descriptive, deductive, inductive methods, techniques and instruments that allowed to obtain true information about the popular businesses of the El Triunfo parish, knowing the impact that the popular food businesses had on the change of the regime. Therefore, an interview was applied to the director of the SRI to learn about the new RIMPE regime, therefore a survey was applied to the 128 small businesses selected as the population of the El Triunfo parish, the results that were obtained and analyzed exhaustively. during the investigation, where it was shown that taxpayers were unaware of the new tax regime, consequently some businesses have not completed their tax obligations for that reason, which emphasized the need to provide owners of popular food businesses with plan instructions of training in the same that consists of clear information accessible using simple language and examples of specific cases related to the popular businesses of the El Triunfo Parish.